2018
DOI: 10.1038/s41467-018-07524-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide mega-analysis identifies 16 loci and highlights diverse biological mechanisms in the common epilepsies

Abstract: The epilepsies affect around 65 million people worldwide and have a substantial missing heritability component. We report a genome-wide mega-analysis involving 15,212 individuals with epilepsy and 29,677 controls, which reveals 16 genome-wide significant loci, of which 11 are novel. Using various prioritization criteria, we pinpoint the 21 most likely epilepsy genes at these loci, with the majority in genetic generalized epilepsies. These genes have diverse biological functions, including coding for ion-channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
221
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 371 publications
(243 citation statements)
references
References 81 publications
(122 reference statements)
7
221
1
4
Order By: Relevance
“…We then generated polygenic risk scores for generalized (GE-PRS) and focal epilepsy (FE-PRS) for all UKB individuals using single-nucleotide polymorphism (SNP) weights derived from summary statistics of the International League Against Epilepsy (ILAE) Consortium on Complex Epilepsies GWAS for GE and FE [17]. The SNPs were pruned based on P<0.5.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…We then generated polygenic risk scores for generalized (GE-PRS) and focal epilepsy (FE-PRS) for all UKB individuals using single-nucleotide polymorphism (SNP) weights derived from summary statistics of the International League Against Epilepsy (ILAE) Consortium on Complex Epilepsies GWAS for GE and FE [17]. The SNPs were pruned based on P<0.5.…”
Section: Plos Onementioning
confidence: 99%
“…GWASs of each vertex's thickness and area were performed using PLINKv1.9 [20], with adjustment for age, age 2 , sex, scanning site, and the first four genetic principal components of ancestry. Next, we estimated the genetic correlation between each vertex's thickness and surface area and the GWAS summary statistics for GE and FE [17], using LD-score regression [28]. The resulting vertexwise genetic correlation maps of cortical morphology with epilepsy were tested for correlation with each other using Spearman correlation.…”
Section: Vertex-wise Genetic Correlationmentioning
confidence: 99%
“…To explore whether changes in mRNA polyadenylation disproportionately affect genes implicated in the pathogenesis of epilepsy, we compiled a set of epilepsy-related genes from three recent independent studies. These studies included: a) genes where mutations cause epilepsy 26 , b) genes with ultra-rare deleterious variations in familial genetic generalized epilepsies (GGE) and non-acquired focal epilepsies (NAFE) 27 and c) genes localized in loci associated with epilepsy 28 (Supplementary Table 2). Remarkably, transcripts displaying poly(A) tail shortening showed an enrichment in genes implicated in epilepsy at both time-points, post status epilepticus and during epilepsy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Genes with ultra-rare deleterious variation in familial genetic generalized epilepsy (GGE) and non-acquired focal epilepsy (NAFE) (n = 18); we chose the most significant genes per group (top 15) 27 . Genes localized in loci associated with epilepsy (n = 21); the 21 most likely epilepsy genes at these loci, with the majority in genetic generalized epilepsies, were selected 28 . The complete set of epilepsy-related genes used in our study is shown in Supplementary Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…New transformative treatments could be developed by understanding the genetic associations conferring risk or protective effects. In addition to rapid expansion of epilepsy-associated gene list discovered mainly with monogenic causes of seizures, human GWAS studies of generalized epilepsy identified more than a dozen novel genome-wide significant loci and biological plausible candidate genes [4][5][6] . However, human GWAS approaches have had limited success in identifying risk loci associated with certain forms of epilepsy (e.g.…”
Section: Introductionmentioning
confidence: 99%